2005
DOI: 10.1080/10623320500191745
|View full text |Cite
|
Sign up to set email alerts
|

Functional Characteristics of Coronary Vasomotor Function Following Intramyocardial Gene Therapy with Naked DNA Encoding for Vascular Endothelial Growth Factor165

Abstract: Vascular endothelial growth factor (VEGF) is a potent angiogenic factor. VEGF gene therapy improves perfusion of ischemic myocardium in experimental models and possibly in patients with end-stage coronary artery disease. In addition to its proliferative and migratory effect on endothelial cells, it also activates and up-regulates endothelial nitric oxide synthase (eNOS). Therefore, the authors investigated coronary endothelium-dependent vasodilatation in patients before and after VEGF gene therapy. The effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2006
2006
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 6 publications
(10 reference statements)
0
4
0
Order By: Relevance
“…VEGF plays important roles in vascular protection 30, 31, hemostasis 32, 33, microvascular permeability 3436, wound repair 37, angiogenesis of ischemic tissue 38, 39, and also regulates vasomotor tone by regulating eNOS activity 4044. In ECs, VEGF induces NO production through PI3K-Akt-mediated phosphorylation of eNOS at S1179 40, 41, 45.…”
mentioning
confidence: 99%
“…VEGF plays important roles in vascular protection 30, 31, hemostasis 32, 33, microvascular permeability 3436, wound repair 37, angiogenesis of ischemic tissue 38, 39, and also regulates vasomotor tone by regulating eNOS activity 4044. In ECs, VEGF induces NO production through PI3K-Akt-mediated phosphorylation of eNOS at S1179 40, 41, 45.…”
mentioning
confidence: 99%
“…The use of endothelial cells for therapeutic intervention has focused on engraftment and expansion of infused progenitor cells (Alobaid et al 2005) or as a target for gene transfer to express endogenously produced proteins (Pelisek et al 2003;Tio et al 2005). Moreover, the movement of these technologies from bench-to-bedside using endothelial cells has been slow to occur (Hwa et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Therapeutic potential of angiogenic growth factors to promote neovascularization The approach of therapeutic angiogenesis is to amplify adaptive neovascularization and perfusion in tissues compromised by ischaemia. 33,34 Studies performed in animal models, [35][36][37][38][39][40] and more recently in patients, 41 have shown that administration of angiogenic growth factors indeed could be employed to augment perfusion and collateral flow, with the different mechanisms thought to be involved: (1) proliferation and migration of resident endothelial cells followed by formation of new blood vessels; (2) remodelling of pre-existing collaterals; (3) improvement of the vasomotor function of large and small-sized arteries by influence on endothelial cell function [42][43][44] ; (4) tissue regeneration by promotion of endogenous vascular progenitor cell mobilization from the BM. [45][46][47] Candidate angiogenic growth factors A number of different growth factors have demonstrated angiogenic potential, including VEGF, FGF, hepatocyte growth factor (HGF), insulinlike growth factor (IGF), granulocyte colonystimulating factor (G-CSF), placental growth factor (PlGF), ANG-1, PDGF, certain interleukins as well as certain transcription factors such as HIF-1α.…”
Section: Therapeutic Angiogenesismentioning
confidence: 99%